2010
DOI: 10.1177/0961203309361351
|View full text |Cite
|
Sign up to set email alerts
|

Anti-phospholipid antibody mediated fetal loss: still an open question from a pathogenic point of view

Abstract: Antiphospholipid antibodies (aPL) are associated with recurrent miscarriages and pregnancy complications, however their pathogenic mechanisms are still matter of research. Thrombotic events at the placental level cannot explain all of the clinical manifestations. It has been suggested that aPL may be responsible for a local acute inflammatory response mediated by complement activation and neutrophil infiltration eventually leading to fetal loss. However histological and immunohistological studies on human plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“…Treatment of these patients is based on the use of platelets antiaggregants and anticoagulants aimed to prevent placental thrombotic events that would ultimately lead to miscarriage. Nevertheless, the participation of β2GP1-dependent non-thrombotic events that would be responsible for the defective placentation observed in APS [4][5][6], would lead to reformulation of the treatment currently applied to these patients. It is worth noting that, although the number of patients included in the present study may seem somewhat low, this is due to the fact that we have been very strict as regards the inclusion criteria applied, thus partly explaining the amplitude of the confidence interval obtained.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of these patients is based on the use of platelets antiaggregants and anticoagulants aimed to prevent placental thrombotic events that would ultimately lead to miscarriage. Nevertheless, the participation of β2GP1-dependent non-thrombotic events that would be responsible for the defective placentation observed in APS [4][5][6], would lead to reformulation of the treatment currently applied to these patients. It is worth noting that, although the number of patients included in the present study may seem somewhat low, this is due to the fact that we have been very strict as regards the inclusion criteria applied, thus partly explaining the amplitude of the confidence interval obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Although placental thrombotic events may play an important role [3], it is nowadays assumed that non-thrombotic mechanisms would be the main cause for the defective placentation observed in patients with antiphospholipid syndrome (APS) [4][5][6]. APS is an autoimmune disease characterized by arterial/venous thrombosis and/or obstetric complications, associated to the persistent presence of anticardiolipins (ACA) and/or lupus anticoagulant (LA) and/or anti-2 glycoprotein 1(a-2GP1) [7].…”
Section: Introductionmentioning
confidence: 99%
“…3596 g), while they found no significant difference between mothers with CD and healthy women in relation to birth weight (3447 g vs. 3596 g) (19). The risk of developing IUGR is fivefold higher in case of fathers with CD than in the general population (11 % vs. 2.5 %) (71,76).…”
Section: Celiac Disease In Relation To Reproductive Failuresmentioning
confidence: 95%
“…Thrombosis at the placental level cannot elucidate all of the clinical manifestations (Meroni et al, 2010). It has been suggested that aPL may be responsible for a local acute inflammatory response mediated by complement activation (Sotoudeh Jahromi, 2007a;Meroni et al, 2010) and neutrophil infiltration eventually leading to fetal loss (Meroni et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Thrombosis at the placental level cannot elucidate all of the clinical manifestations (Meroni et al, 2010). It has been suggested that aPL may be responsible for a local acute inflammatory response mediated by complement activation (Sotoudeh Jahromi, 2007a;Meroni et al, 2010) and neutrophil infiltration eventually leading to fetal loss (Meroni et al, 2010). In addition to the Classical Lupus Anticoagulant (LAC) and AntiCardiolipin Antibodies (ACA), other anti-Phospholipid Antibodies (aPL) were shown to target anionic phospholipids and other plasma proteins, including phosphatidylethanolamine, protein C, protein S, ß 2 -Glycoprotein I (GPI) and annexin V (Tincani et al, 2010).…”
Section: Introductionmentioning
confidence: 99%